S‐Doped Carbon Nanospheres: An Efficient Electrocatalyst toward Artificial N2 Fixation to NH3. Issue 6 (7th December 2018) - Xia, Li; Wu, Xiufeng; Wang, Yuan; Niu, Zhiguo; Liu, Qian; Li, Tingshuai; Shi, Xifeng; Asiri, Abdullah M.; Sun, Xuping
Abstract: Industrial NH3 synthesis mainly relies on the carbon‐emitting Haber–Bosch process operating under severe conditions. Electrocatalytic N2 to NH3 fixation at ambient conditions is an attractive approach to reduce energy consumption and avoid direct carbon emission. In this communication, it is reported that the S‐doped carbon nanosphere (S‐CNS) acts as an efficient and stable nitrogen reduction reaction (NRR) catalyst for ambient N2 to NH3 conversion with excellent selectivity. In 0.1 m Na2 SO4, the S‐CNS achieves a large NH3 yield of 19.07 μg h −1 mg −1 cat. and a high Faradic efficiency of 7.47% at –0.7 V versus reversible hydrogen electrode, much higher than those of undoped CNS (3.70 μg h −1 mg −1 cat., 1.45%). Notably, this catalyst also demonstrates high electrochemical and structure stability. Abstract : S‐doped carbon nanospheres (S‐CNSs) are an efficient catalyst for electrochemical N2 fixation to NH3 . In 0.1 m Na2 SO4, the S‐CNS attains a large NH3 yield of 19.07 µg h −1 mg −1 cat. and a high Faradic efficiency of 7.47% at –0.7 V vs RHE. Notably, this catalyst demonstrates high electrochemical and structure stabilty.